Later lexical development in Hebrew peer talk - Zwilling, Racheli; Ravid, Dorit (Frontiers in Language Sciences, 2025)
This study examines later lexical development in Hebrew, focusing on the spoken discourse of school-aged participants. A new corpus was recorded and transcribed for this research, consisting of triadic peer conversations among children and adolescents. The study included 72 native Hebrew speakers, divided into four age/grade-level groups: 1st−2nd graders, 3rd−4th graders, 5th−6th graders, and 7th−8th graders. Two categories of lexical items were analyzed in the corpus, which contained nearly 100,000 words: content words (nouns, verbs, adjectives, and lexical adverbials) and discourse words (discourse markers, social words, and address forms). The study explores the distributional changes of these lexical categories across development, providing insights into language development and socio-cognitive growth during the school years.